Digital prototyping: a Case study on its viability in enhancing small and medium ceramic industries - Ab. Aziz Shuaib; Olalere, Folasayo Enoch (2013)
Small and Medium Industries are important to almost all economies in the world, particularly to developing countries and, within that broad category, especially to those with major employment and income distribution challenges. They contribute to the output and creation of jobs; also they are a nursery for the large firms of the future. Hence, this paper seeks to explore further on findings from previous research work which ex-perimentally investigates the viability of digital and rapid prototyping in small and medium scale ceramic industries. The findings from the re-search revealed that digital and rapid prototyping are viable in reducing development time and improving prototype accuracy; however, the re-search shows that rapid prototyping is an expensive approach and thus, proposed conventional method of prototyping (hand turning and carving) to be still valid in small and medium ceramic industries. Therefore, based on these findings, this further research seeks to explore how digital pro-totyping can be used to enhance conventional method of prototyping. Rather than replacing conventional method with digital and rapid prototyp-ing, this research tried to enhance the conventional method by integrating it with digital prototyping. The findings from this further research re-vealed that the conventional method of prototyping can be enhanced by integrating digital prototyping (3D CAD model) into development process as this will help designers/carvers to visualize products digitally throughout product development process, thereby communicating the whole con-cept and idea being proposed. Also, this will build their creative skills and make them think “outside the box” thereby making them capable of pro-ducing innovative and exclusive prototypes/products.